Comparison of the Functions of Presidential Decrees Before and After the Law on the Formation of Legislation - Ndaru Hidayatulloh; Sony Maulana Sikumbang (JURNAL PENDIDIKAN IPS, 2025)
This paper aims to compare the functions of Presidential Decrees before and after the enactment of the Law on the Formation of Legislation. As the head of government and head of state, the President possesses legal instruments in the form of determinations and regulations, one of which is the Presidential Decree. Presidential Decrees are not only understood as beschikking norms but can also be interpreted as legislation, policy regulations (beleidsregel), administrative decisions, and decisions of a general nature. This study employs a doctrinal legal research method to examine the legal norms in Indonesia and the comparison of the functions of Presidential Decrees before and after the enactment of the Law on the Formation of Legislation. The research findings indicate that prior to the enactment of the Law, Presidential Decrees functioned as legislation and legal instruments to create, modify, or revoke legal relationships. However, following the enactment of the Law on the Formation of Legislation, the function of Presidential Decrees has been narrowed. Presidential Decrees now only serve to determine specific matters related to the creation, modification, or revocation of legal relationships concerning specific subjects and circumstances.